EFTUD2 haploinsufficiency leads to syndromic oesophageal atresia. Issue 12 (27th November 2012) - Gordon, Christopher T; Petit, Florence; Oufadem, Myriam; Decaestecker, Charles; Jourdain, Anne-Sophie; Andrieux, Joris; Malan, Valérie; Alessandri, Jean-Luc; Baujat, Geneviève; Baumann, Clarisse; Boute-Benejean, Odile; Caumes, Roseline; et al.
Abstract : Background: Oesophageal atresia (OA) and mandibulofacial dysostosis (MFD) are two congenital malformations for which the molecular bases of syndromic forms are being identified at a rapid rate. In particular, the EFTUD2 gene encoding a protein of the spliceosome complex has been found mutated in patients with MFD and microcephaly (MIM610536). Until now, no syndrome featuring both MFD and OA has been clearly delineated. Results: We report on 10 cases presenting with MFD, eight of whom had OA, either due to de novo 17q21.31 deletions encompassing EFTUD2 and neighbouring genes or de novo heterozygous EFTUD2 loss-of-function mutations. No EFTUD2 deletions or mutations were found in a series of patients with isolated OA or isolated oculoauriculovertebral spectrum (OAVS). Conclusions: These data exclude a contiguous gene syndrome for the association of MFD and OA, broaden the spectrum of clinical features ascribed to EFTUD2 haploinsufficiency, define a novel syndromic OA entity, and emphasise the necessity of mRNA maturation through the spliceosome complex for global growth and within specific regions of the embryo during development. Importantly, the majority of patients reported here with EFTUD2 lesions were previously diagnosed with Feingold or CHARGE syndromes or presented with OAVS plus OA, highlighting the variability of expression and the wide range of differential diagnoses.